(untitled) (AYUSHDHARA, 2025)
Garbhini Chhardi (pregnancy-induced nausea and vomiting) is a prevalent condition that leads to discomfort, dehydration, and digestive disturbances in pregnant women. This article explores the therapeutic role of Bilva Majja capsules combined with Lajambu in managing this condition through an Ayurvedic approach. Bilva Majja is known for its Vata-Anulomaka, Deepana and Pachana properties, which help regulate Vata dosha, stimulate the digestive system, and reduce nausea. Lajambu, made from parched rice (Laja), offers Trishna Shamaka and Kaphaghna effects, alleviating excessive thirst and balancing Kapha, which are often associated with nausea and vomiting during pregnancy. The article focuses on the synergistic action of these two ingredients, emphasizing how their combined use addresses the underlying causes of Garbhini Chhardi. By improving digestion, balancing Doshas, and rehydrating the body, this remedy helps in reducing the frequency and intensity of vomiting. Furthermore, it provides a practical, easy-to-consume solution that aligns with the fast-paced lifestyle of modern-day pregnancy. This Ayurvedic combination presents a safe and natural approach to managing Garbhini Chhardi, ensuring comfort and well-being for both the mother and the fetus.